A flexible thermo-electromagnetic energy conversion film with enhanced refrigeration performance and a preparation method thereof

By introducing magnetic nanoparticles into the flexible thermoelectric film, forming a thermo-electromagnetic composite powder and preparing a wet film, the problem of insufficient performance of flexible thermoelectric films in the prior art is solved, and a flexible thermo-electromagnetic energy conversion film with high performance and high refrigeration capability is achieved.

CN113725348BActive Publication Date: 2025-02-28WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110915044.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-10
Publication Date
2025-02-28
Estimated Expiration
2041-08-10

AI Technical Summary

Technical Problem

The prior art is difficult to produce high-performance flexible thermoelectric films that fully meet application requirements, especially with challenges in terms of cost and consistency.

Method used

Thermoelectronic material powder is mixed with magnetic nanoparticles to form a thermoelectromagnetic composite powder and mixed with a binder solution to prepare a thermoelectromagnetic ink. A thermoelectromagnetic wet film is prepared on the substrate using wet film technology, and then dried and hot-pressed sintered to obtain a flexible thermoelectromagnetic energy conversion film with enhanced refrigeration performance.

Benefits of technology

The thermoelectric performance of flexible thermoelectric energy conversion films and the cooling capacity near room temperature are significantly improved, and performance parameters such as conductivity, power factor and refrigeration temperature difference are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003205317060000011
    Figure HDA0003205317060000011
  • Figure HDA0003205317060000012
    Figure HDA0003205317060000012
  • Figure HDA0003205317060000021
    Figure HDA0003205317060000021
Patent Text Reader

Abstract

The present invention relates to a flexible thermo-electromagnetic energy conversion film with enhanced refrigeration performance and a preparation method thereof. First, thermoelectric material powder and magnetic nanoparticles are ball-milled and mixed evenly under a protective atmosphere to obtain a thermo-electromagnetic composite powder; then the thermo-electromagnetic composite powder is added to a binder solution and mixed evenly to obtain a thermo-electromagnetic ink; finally, a thermo-electromagnetic wet film is printed on a substrate using the thermo-electromagnetic ink, and a flexible thermo-electromagnetic energy conversion film is obtained after drying and hot pressing and sintering. The present invention introduces magnetic nanoparticles into the thermoelectric film to induce a new thermo-electromagnetic coupling effect, which not only gives the film certain magnetic properties, but also significantly improves its thermoelectric performance and refrigeration capacity near room temperature. The technology provided by the present invention is expected to promote the development and application of active heat dissipation technology in all-solid-state refrigeration based on thermo-electromagnetic energy conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a flexible thermo-electromagnetic energy conversion film with enhanced refrigeration performance and a preparation method thereof. Background Art

[0002] Thermoelectric materials are a new energy material that can achieve direct conversion of heat and electricity. Thermoelectric conversion devices made of thermoelectric materials can be divided into two types according to the direction of heat flow: out-of-plane thermoelectric devices and in-plane thermoelectric devices. The heat flow direction of out-of-plane thermoelectric devices is perpendicular to the substrate surface, and has the advantages of large heat absorption area and high heat utilization rate. They have been applied to automobile exhaust waste heat power generation, solar full-spectrum high-efficiency power generation, deep space power supply, thermoelectric refrigerators and other fields. However, out-of-plane thermoelectric devices also have some disadvantages, such as poor flexibility, large size, low power density and difficulty in application in irregular, narrow and high heat flux density spaces. The heat flow direction of in-plane thermoelectric devices is parallel to the substrate surface, and has the advantages of good flexibility and small size. They are expected to be applied to the fields of efficient heat dissipation in the surface of mobile phone chips, self-powered bidirectional temperature control sensors, low-power self-powered Internet of Things nodes, self-powered flexible wearable devices, etc. At present, there are no commercial products for in-plane thermoelectric devices. One of the main reasons is that high-performance thermoelectric films that fully meet application requirements have not been prepared.

[0003] Currently, thermoelectric films can be prepared through technologies such as evaporation coating, magnetron sputtering, pulsed laser deposition and chemical vapor deposition, and their thermoelectric performance is usually very high, and some are even close to bulk thermoelectric materials with the same components. However, it is undeniable that the cost of the above-mentioned deposition preparation technology is relatively high and the consistency of the film is poor. In addition, slurry or ink can also be used through wet film forming methods such as brushing, spin coating, inkjet printing and screen printing to prepare highly flexible thermoelectric films at low cost and in a controllable manner, but its thermoelectric conversion performance, especially the electrical transport performance, is seriously deteriorated. Although scientific researchers have explored a variety of solutions to this problem, they still cannot fully meet the needs of practical applications.

[0004] Recently, the research group of the inventor of this application discovered a new mechanism for enhancing thermoelectric conversion performance through the thermoelectromagnetic coupling effect in the study of bulk thermoelectric materials, which is expected to provide a new idea for the study of thermoelectric thin films. 12 O 19 The new thermo-electromagnetic coupling effect produced by the ferromagnetic-paramagnetic transition of magnetic nanoparticles can effectively suppress the performance degradation of medium-temperature thermoelectric materials filled with CoSb3 due to intrinsic excitation. The electron multiple scattering effect produced by superparamagnetic Co nanoparticles is used to achieve the coordinated regulation of phonon and electron transport in filled CoSb3. The superparamagnetic enhanced thermoelectric potential effect produced by superparamagnetic Fe3O4 magnetic nanoparticles in room-temperature thermoelectric material p-type Bi2Te3 significantly improves the electrothermal transport performance of the composite material.

[0005] Based on the above research results, it can be seen that introducing magnetic nanoparticles is an effective way to improve the thermoelectric properties of bulk thermoelectric materials. However, there are significant differences between bulk thermoelectric materials and flexible thermoelectric films in terms of composition, structure, and preparation methods. Whether this method can be used for flexible thermoelectric films and improve their thermoelectric performance needs further exploration and verification, and no relevant reports have been found so far. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a flexible thermoelectromagnetic energy conversion film with enhanced refrigeration performance, the preparation method comprising the following steps: (a) mixing thermoelectric material powder and magnetic nanoparticles to obtain thermoelectromagnetic composite powder; (b) mixing the thermoelectromagnetic composite powder with a binder solution to obtain thermoelectromagnetic ink; (c) using the thermoelectromagnetic ink to prepare a thermoelectromagnetic wet film on a substrate, followed by drying and hot pressing sintering.

[0007] Furthermore, the thermoelectric material powder in step (a) is p-type or n-type, specifically selected from Bi2Te3-based thermoelectric materials and Sb2Te3-based thermoelectric materials. The particle size of the thermoelectric material powder does not exceed 120 μm.

[0008] Furthermore, the magnetic nanoparticles in step (a) are specifically magnetic nanomaterials of ferromagnetic metals Fe, Co or Ni.

[0009] Further, in step (a), the mixing method of the thermoelectric material powder and the magnetic nanoparticles is ball milling, the ball milling medium is an alcohol solvent (such as anhydrous ethanol), vacuum is evacuated and a protective gas (such as Ar) is introduced during ball milling, the ball milling speed is 100-400r / min, and the ball milling time is 0.5-12h. Relative to mixing methods such as ultrasonic dispersion, mechanical stirring, and manual grinding, ball milling mixing is more likely to achieve the dispersion uniformity of the composite powder, and the powder can be refined. The introduction of alcohol solvents and protective atmosphere can prevent the thermoelectric powder and the magnetic particles from being oxidized during the ball milling process.

[0010] Furthermore, in step (a), the mass of magnetic nanoparticles in the thermo-electromagnetic composite powder does not exceed 10%.

[0011] Furthermore, the raw materials for preparing the binder solution in step (b) include a binder and a solvent, and a curing agent, a catalyst or other surface additives may be added. The binder is selected from at least one of acrylic resin, polyurethane resin, epoxy resin and cellulose resin, the solvent is selected from at least one of N-methylpyrrolidone, ethanol, butyl glycidyl ether, terpineol and dimethyl ester, the curing agent is selected from at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride and pyromellitic dianhydride, and the catalyst is selected from at least one of 2-ethyl-4-methylimidazole and 1-cyanoethyl-2-ethyl-4-methylimidazole. The curing agent and catalyst are added only to ensure the curing of the epoxy resin; the addition of other additives is to make the ink or paste more suitable for printing.

[0012] Furthermore, the concentration of the binder in the binder solution is 1-400 g / L, the concentration of the curing agent does not exceed 400 g / L, and the concentration of the catalyst does not exceed 100 g / L.

[0013] Furthermore, in step (b), the mass ratio of the thermo-electromagnetic composite powder and the binder solution when mixed is 1:0.2-0.6, and the mixing method is to add the thermo-electromagnetic composite powder to the binder solution, and then mechanically stir and ultrasonically mix them evenly.

[0014] Furthermore, in step (c), the thermal electromagnetic wet film is prepared on the substrate by any one of screen printing, 3D printing, gravure printing, inkjet printing or dispensing printing, and the material of the substrate is selected from any one of polyimide, polyethylene terephthalate, polyethylene naphthalate, and glass cloth.

[0015] Furthermore, in step (c), the obtained thermo-electromagnetic wet film is heated to 50-150° C. for drying, and then heated and hot-pressed for sintering, wherein the sintering temperature does not exceed the tolerance temperature of the substrate and the hot-pressing pressure is 1-20 MPa.

[0016] The present invention also provides a flexible thermo-electromagnetic energy conversion film material with enhanced refrigeration performance.

[0017] The mechanism of the present invention lies in: the charge transfer, magnetoresistance effect, defect reaction and interface bridging effect between ferromagnetic metal nanoparticles and the matrix components of the thermoelectric material realize the coordinated regulation of the electrical transport performance and thermal transport performance of the thermoelectromagnetic energy conversion film, thereby significantly improving the thermoelectric performance and cooling capacity of the flexible thermoelectromagnetic energy conversion film near room temperature.

[0018] Compared with the prior art, the advantages of the present invention are embodied in the following points: (1) By introducing magnetic nanoparticles into the thermoelectric film, the induced new thermoelectromagnetic coupling effect not only gives the flexible thermoelectromagnetic composite film certain magnetic properties, but also significantly improves the thermoelectric performance and the cooling capacity near room temperature; (2) After the introduction of magnetic nanoparticles, the performance parameters such as the electrical conductivity, power factor, and cooling temperature difference of the thermoelectromagnetic energy conversion film and the assembled single-arm device are greatly improved; (3) The entire preparation method is simple and controllable, and is expected to promote the development of active heat dissipation technology based on all-solid-state refrigeration in-plane based on thermoelectromagnetic energy conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 (ac) is Fe / Bi 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion film (Fe02), Bi 0.5 Sb 1.5 The relationship between the conductivity, Seebeck coefficient, power factor and test temperature of Te3 thermoelectric film (Fe00). Figure 1 (d) is a graph showing the relationship between the hot and cold end temperatures of a single-arm device assembled based on the two aforementioned films and the test time.

[0020] Figure 2 Co / Bi 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion film (Co02), Bi 0.5 Sb 1.5 The relationship between the conductivity, Seebeck coefficient and power factor of Te3 thermoelectric film (Co00) and the test temperature. Figure 2 (d) is a graph showing the relationship between the hot and cold end temperatures of a single-arm device assembled based on the two aforementioned films and the test time.

[0021] Figure 3 for Ni / Bi 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion film (Ni01), Bi 0.5 Sb 1.5 The relationship between the conductivity, Seebeck coefficient and power factor of Te3 thermoelectric film (Ni00) and the test temperature. Figure 3 (d) is a graph showing the relationship between the hot and cold end temperatures of a single-arm device assembled based on the two aforementioned films and the test time. DETAILED DESCRIPTION

[0022] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with specific embodiments and drawings.

[0023] Example 1

[0024] Preparation of Fe / Bi by adding 0.2wt% Fe magnetic nanoparticles 0.5 Sb 1.5 The process of Te3 thermo-electromagnetic energy conversion film is as follows:

[0025] Bismuth telluride (Bi 0.5 Sb 1.5 Te3, BST) crystal rods were crushed and screened to obtain BST thermoelectric powder with a particle size of less than 120μm. 9.98g BST powder and 0.02g Fe magnetic nanoparticles were accurately weighed and added to a high-energy ball mill. 50g anhydrous ethanol was added as the ball milling medium. After vacuuming, Ar gas was introduced for protection. The ball milling process parameters were: speed 200r / min, ball milling time 2h. After ball milling, the mixture was centrifuged and dried to obtain Fe / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic composite powder.

[0026] Accurately weigh 0.612 g of bisphenol F diglycidyl ether epoxy resin, 0.521 g of methyl hexahydrophthalic anhydride, 0.123 g of 2-ethyl-4-methylimidazole, and 1.8 g of butyl glycidyl ether, and mix them evenly to obtain an epoxy resin adhesive solution.

[0027] 10g Fe / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic composite powder was added to 3.056g epoxy resin binder solution and mixed, first mechanically stirred and then ultrasonically dispersed to obtain a uniform and stable Fe / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic ink.

[0028] The polyimide substrate was ultrasonically cleaned in anhydrous ethanol for 15 min and then dried. Then, the Fe / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic ink was printed on the substrate, and the obtained wet film was vacuum dried at 80°C and transferred to a hot press machine for hot pressing at 10MPa and 543K for 4h to obtain Fe / Bi 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion film (Fe02).

[0029] Bi-ion nanoparticles without Fe were prepared under the same process conditions. 0.5 Sb 1.5 Te3 thermoelectric thin film (Fe00).

[0030] Fe / Bi were tested separately 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion thin film and Bi0.5 Sb 1.5 The electrical transport properties and refrigeration performance of Te3 thermoelectric films near room temperature are shown in the following table. Figure 1 shown.

[0031] from Figure 1 (ac) It can be seen that Fe / Bi 0.5 Sb 1.5 The conductivity of Te3 thermoelectromagnetic energy conversion film is higher than that of Bi 0.5 Sb 1.5 Te3 thermoelectric film is significantly improved, while the Seebeck coefficient is slightly reduced, but the final power factor is significantly improved; using Fe / Bi 0.5 Sb 1.5 The cooling temperature difference of the single-arm device prepared by Te3 thermoelectromagnetic energy conversion film is better than that of Bi 0.5 Sb 1.5 The single-arm device prepared by Te3 thermoelectric thin film has been improved by 1.7 times, with obvious improvement effect.

[0032] Example 2

[0033] Preparation of Co / Bi by adding 0.2wt% Co magnetic nanoparticles 0.5 Sb 1.5 The process of Te3 thermo-electromagnetic energy conversion film is as follows:

[0034] Bismuth telluride (Bi 0.5 Sb 1.5 Te3, BST) crystal rods were crushed and screened to obtain BST thermoelectric powder with a particle size of less than 120μm. 9.98g BST powder and 0.02g Co magnetic nanoparticles were accurately weighed and added to a high-energy ball mill. 50g anhydrous ethanol was added as the ball milling medium. After vacuuming, Ar gas was introduced for protection. The ball milling process parameters were: speed 200r / min, ball milling time 2h. After ball milling, the mixture was centrifuged and dried to obtain Co / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic composite powder.

[0035] Accurately weigh 0.2 g of bisphenol F diglycidyl ether epoxy resin, 0.17 g of methyl hexahydrophthalic anhydride, 0.04 g of 2-ethyl-4-methylimidazole, and 0.9 g of butyl glycidyl ether, and mix them evenly to obtain an epoxy resin adhesive solution.

[0036] Will 4g Co / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic composite powder was added to 1.31g epoxy resin binder solution and mixed, first mechanically stirred and then ultrasonically dispersed to obtain a uniform and stable Co / Bi 0.5 Sb 1.5Te3 thermo-electromagnetic ink.

[0037] The polyimide substrate was ultrasonically cleaned in anhydrous ethanol for 5 min and then dried. Then the Co / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic ink was printed on the substrate, and the obtained wet film was dried in vacuum at 90°C and placed in a hot press for 4 h at 8 MPa and 573 K to obtain Co / Bi 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion thin film (Co02).

[0038] Bi-free magnetic nanoparticles without Co were prepared under the same process conditions. 0.5 Sb 1.5 Te3 thermoelectric thin film (Co00).

[0039] Co / Bi were tested separately 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion thin film and Bi 0.5 Sb 1.5 The electrical transport properties and refrigeration performance of Te3 thermoelectric films near room temperature are shown in the following table. Figure 2 shown.

[0040] from Figure 2 (ac) It can be seen that Co / Bi 0.5 Sb 1.5 The conductivity of Te3 thermoelectromagnetic energy conversion film is higher than that of Bi 0.5 Sb 1.5 Te3 thermoelectric film is significantly improved, while the Seebeck coefficient is slightly reduced, but the final power factor is significantly improved; using Co / Bi 0.5 Sb 1.5 The cooling temperature difference of the single-arm device prepared by Te3 thermoelectromagnetic energy conversion film is better than that of Bi 0.5 Sb 1.5 The single-arm device made of Te3 thermoelectric film has been improved by 1.5 times, and the improvement effect is also obvious.

[0041] Example 3

[0042] Preparation of Ni / Bi by adding 0.1wt% Ni magnetic nanoparticles 0.5 Sb 1.5 The process of Te3 thermo-electromagnetic film is as follows:

[0043] Bismuth telluride (Bi 0.5 Sb 1.5Te3, BST) crystal rods were crushed and screened to obtain BST thermoelectric powder with a particle size of less than 120μm. 9.98g BST powder and 0.01g Ni magnetic nanoparticles were accurately weighed and added to a high-energy ball mill. 50g anhydrous ethanol was added as the ball milling medium. After vacuuming, Ar gas was introduced for protection. The ball milling process parameters were: speed 200r / min, ball milling time 2h. After ball milling, the mixture was centrifuged and dried to obtain Ni / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic composite powder.

[0044] Accurately weigh 0.2 g of bisphenol F diglycidyl ether epoxy resin, 0.17 g of methyl hexahydrophthalic anhydride, 0.04 g of 2-ethyl-4-methylimidazole, and 0.9 g of butyl glycidyl ether, and mix them evenly to obtain an epoxy resin adhesive solution.

[0045] Will 4g Ni / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic composite powder was added to 1.31g epoxy resin binder solution and mixed, first mechanically stirred and then ultrasonically dispersed to obtain a uniform and stable Ni / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic ink.

[0046] The polyimide substrate was ultrasonically cleaned in anhydrous ethanol for 5 minutes and then dried. Then, the Ni / Bi 0.5 Sb 1.5 Te3 thermo-electromagnetic ink was printed on the substrate, and the obtained wet film was dried in vacuum at 120°C and placed in a hot press for 5 h at 8 MPa and 573 K to obtain Ni / Bi 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion thin film (Ni01).

[0047] Bi without Ni magnetic nanoparticles was prepared under the same process conditions. 0.5 Sb 1.5 Te3 thermoelectric thin film (Ni00).

[0048] Ni / Bi were tested separately 0.5 Sb 1.5 Te3 thermoelectromagnetic energy conversion thin film and Bi 0.5 Sb 1.5 The electrical transport properties and refrigeration performance of Te3 thermoelectric films near room temperature are shown in the following table. Figure 3 shown.

[0049] from Figure 3 (ac) It can be seen that Ni / Bi 0.5 Sb 1.5The conductivity of Te3 thermoelectromagnetic film is higher than that of Bi 0.5 Sb 1.5 Te3 thermoelectric film is significantly improved, while the Seebeck coefficient is slightly reduced, but the final power factor is significantly improved; using Ni / Bi 0.5 Sb 1.5 The cooling temperature difference of the single-arm device prepared by Te3 thermoelectromagnetic film is better than that of Bi 0.5 Sb 1.5 The single-arm device made of Te3 thermoelectric film has been improved by 2.5 times, and the improvement effect is more prominent.

Claims

1. A method for preparing a flexible thermo-electromagnetic energy conversion film with enhanced refrigeration performance, characterized in that The preparation method comprises the following steps: (a) mixing thermoelectric material powder and magnetic nanoparticles and ball milling them, wherein the ball milling medium is an alcohol solvent, vacuumizing and introducing a protective gas during ball milling, and obtaining a thermo-electromagnetic composite powder after ball milling; wherein the thermoelectric material powder is p-type or n-type, specifically selected from Bi2Te3-based thermoelectric materials and Sb2Te3-based thermoelectric materials, and the magnetic nanoparticles are specifically magnetic nanoparticles of ferromagnetic metals Fe, Co or Ni; (b) adding the thermo-electromagnetic composite powder to a binder solution, followed by mechanical stirring and ultrasonic mixing to obtain a thermo-electromagnetic ink; wherein the raw materials for preparing the binder solution include a binder, a solvent, a curing agent, and a catalyst, wherein the binder is selected from at least one of acrylic resin, polyurethane resin, epoxy resin, and cellulose resin, the solvent is selected from at least one of N-methylpyrrolidone, ethanol, butyl glycidyl ether, pinene alcohol, and dimethyl ester, the curing agent is selected from at least one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and pyromellitic dianhydride, and the catalyst is selected from at least one of 2-ethyl-4-methylimidazole and 1-cyanoethyl-2-ethyl-4-methylimidazole; (c) Using any one of screen printing, 3D printing, gravure printing, inkjet printing or dispensing printing, a thermo-electromagnetic wet film is prepared on a substrate using thermo-electromagnetic ink, followed by drying and hot pressing and sintering.

2. The preparation method according to claim 1, characterized in that: In step (a), the ball milling speed is 100-400 r / min, and the ball milling time is 0.5-12 h.

3. The preparation method according to claim 1, characterized in that: In step (a), the mass of magnetic nanoparticles in the thermo-electromagnetic composite powder does not exceed 10%.

4. The preparation method according to claim 1, characterized in that: The concentration of the binder in the binder solution is 1-400 g / L, the concentration of the curing agent does not exceed 400 g / L, the concentration of the catalyst does not exceed 100 g / L, and the concentration of other surface additives does not exceed 100 g / L.

5. The preparation method according to claim 1, characterized in that: In step (b), the mass ratio of the thermo-electromagnetic composite powder and the binder solution when mixed is 1:0.2-0.

6.

6. The preparation method according to claim 1, characterized in that: In step (c), the material of the substrate is selected from any one of polyimide, polyethylene terephthalate, polyethylene naphthalate, and glass cloth; the thermal electromagnetic wet film drying temperature is 50-150° C., the sintering temperature does not exceed the tolerance temperature of the substrate, and the hot pressing pressure is 1-20 MPa.

7. A flexible thermo-electromagnetic energy conversion film material with enhanced refrigeration performance, characterized in that: The film material is prepared according to any one of the methods of claims 1-6.

Citation Information

Patent Citations

  • Preparation method of magnetic ink

    CN102277034A

  • A method for preparing a flexible thermoelectric thick film material with excellent electrical transport performanceby adding a sintering aid

    CN109192851A